The Influence of Convertible Bond Financing on the Operating Performance of Chinese Companies - Zhang, Chuxin (2020)
China's convertible bond market has been gradually prospering since 2017. Because of its dual attributes of equity and debt, it is also favored by investors, and the China Securities Regulatory Commission has continuously introduced new policies to encourage the development of the convertible bond market. This article mainly studies the main impact of the issuance of convertible bonds on the operating performance of listed companies and explores the reasons behind the impact This article first uses the Wilcoxon rank-sum test method to test the fluctuations in the operating performance of listed companies that issued convertible bonds from 2010 to 2017. The indicators to measure operating performance include ROA, Profit margin, operating cash flow per share, etc. Multiple indicators. At the same time, this paper selects a control group for the sample group according to multiple dimensions such as industry and BM value to compare the differences between the two groups. This paper takes ROA of listed companies as a substitute variable for operating performance, and regresses ROA and Debt to equity ratio, Proportion of largest shareholders, Book to market value ratio and other variables to explore the reasons that affect the performance of listed companies. The research in this article shows that: The operating iii performance of listed companies after the issuance of convertible bonds from 2010 to 2017 has experienced significant declines in varying degrees, and the above performance reached the highest point at the end of the year before the issuance of bonds or the year of issuance. Significant differences also appeared in some financial indicators during the comparison with the control group. The high level of Proportion of largest shareholders, Book to market value ratio, asset turnover ratio, the more they will promote listing the company's performance is improving. At the same time, the increase in debt to equity ratio, and R&D to income ratio will reduce the performance of listed companies in the short time.